Best Answer

Use the quadratic formula. In x2 + 12x + 13 = 0, a = 1, b = 12 and c = 3. The formula is:

-b +/- √(b2 - 4ac)

----------------------

2a

Thus, x = [-2 +/- √(122 - 4(1)(13))]/2(1) = [-2 +/- √(144 - 52)]/2 = [-2 +/- √92]/2 = -1 +/- √23.

Q: How do you solve x squared plus 12x plus 13 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0

This is not an inequality. This is an equation.12x+7=43 12x=36 x=3

(-3, -5)

It can't be solved because the discriminant of the given quadratic equation is less than zero meaning it has no real roots.

8x squared

Related questions

x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0

4x2 = -12x, divide both sides by 4x: x = -3

This is not an inequality. This is an equation.12x+7=43 12x=36 x=3

(-3, -5)

5x-3 = 11+12x 5x-12x = 11+3 -7x = 14 x = -2

It can't be solved because the discriminant of the given quadratic equation is less than zero meaning it has no real roots.

x2+12x+11=0 (x+11)(x+1)=0 x=-11 or x=-1

8x squared

(x-3)(x-9) = 0

2(x - 2)(x - 4)

Factor. X^2 + 12X X(X + 12) = 0 X = 0 ------------- X + 12 = 0 X = - 12 --------------

12x - 6 = 10x +2 12x - 10x = 2 + 6 2x = 8 x = 4